Analisis Framing Drama Korea “Pyramid Game ” sebagai Gambaran Hierarki Sosial Remaja Korea Selatan - Devi Cindy Claudya Simanjuntak; Angel Damayanti; Silvia Nevane Paramasi (PT. Pustaka Cendekia Publisher, 2025)
Facing the era of information globalization and technological developments, the world is finally facing a rapid change in the flow of information. This is one of the drivers to change the way people think about getting information quickly, accurately and reliably. This research uses a qualitative approach where the qualitative research approach is an activity that places observers in the real world. The type of research used in this study is the descriptive research type. This research will use the method of using the observation method by systematically observing and recording the drama shows.